Assessment the effect of vitamin D supplementation on plasma vitamin D levels, inflammation, and oxidative stress biomarkers based on vitamin D receptor genetic variation in breast cancer survivors: a protocol for clinical trial - Elham kazemian (BMC, 2021)
Abstract Background Both human genes and environmental exposures, due to complex interplay, play important role in the cancer etiology. Vitamin D is associated with a reduced risk of incidence and mortality of several human cancers. This study will aim to investigate the possible effects of individual polymorphisms in vitamin D receptor (VDR) as well as effects of VDR haplotypes on response to vitamin D supplementation in breast cancer survivors. Methods This is an interventional study in which the effects of vitamin D supplementation on plasma vitamin D levels, inflammatory and antioxidant biomarkers and factors associated with cell proliferation, differentiation, damage, and apoptosis will be investigated stratified by variations in VDR genotype. The present study will be conducted on breast cancer survivors referred to the Shohadaye Tajrish hospital and its associated clinics. One hundred ninety-eight breast cancer survivors will receive 4000 IU of vitamin D3 daily for 12 weeks. VDR Fok1, ApaI, TaqI, BsmI, and Cdx-2 genotype will be determined at the end of the study and responses to vitamin D supplements (inflammatory, antioxidant, cell proliferation, differentiation, damage, and apoptosis biomarkers) will be compared between the three subgroups of each VDR polymorphism as well as different VDR haplotype categories. Discussion Genetic variation is a fundamental factor influencing individuals’ divergent responses to diet, nutritional status, metabolic response, and diet-related health disorders. Furthermore, studies of gene and environment interactions will provide a precise and accurate assessments of individuals’ dietary requirements by considering both the genetic and environmental aspects simultaneously. The results of the current study, to some extent, will highlight the discrepancies existing in the findings of different studies regarding vitamin D, VDR, and cancer by considering both the genetic and environmental aspects simultaneously. If responses to vitamin D supplementation could be modified by VDR SNPs, determining the distribution of VDR polymorphisms in both breast cancer survivors and healthy populations will provide a new insight into the vitamin D requirements of individuals to prevent cancer and its related mortality based on their genotypes. Trial registration This trial has been registered on Iranian Registry of Clinical Trials (IRCT) under the identification code: IRCT2017091736244N1, registration date: 2017-11-10, http://www.irct.ir/trial/27153